Dampak Pandemi Terhadap Hasil Belajar Siswa SD Negeri Kassi Kota Makassar - Nurfitri; Perawati Bte Abustang; Cayati; Mochammad Nuer Alim Qalby (Jurnal Elementaria Edukasia, 2023)
After the spread of the COVID-19 outbreak had an effect on the world of education, the forced learning system became an online or online study policy at home. This makes students required to be able to master online learning in order to follow social distancing rules imposed by the government to reduce the spread of Covid-19. This research is classified into the type of correlation research using a quantitative approach. This research was conducted at Kassi Public Elementary School, Makassar City. The sample in this study were all class IVA students at SD Negeri Kassi, Makassar City, which consisted of 27 students, using a simple random sampling technique. The test results at SD Negeri Kassi Makassar City used descriptive statistical analysis, with an average score of 78.70 in the good category, and an average score of 79.52 in the good category. Inferential statistical analysis, online learning normality test results 0.127>0.05 normally distributed, online learning homogeneity test results and learning outcomes 0.923>0.05 (homogeneous), linearity test results are 0.850>0.05 (linear) based on the results of the data then there is a linear influence of online learning and learning outcomes. The results of the hypothesis test showed a sig value of 0.005, with the criteria of sig 0.005 <a 0.05. The conclusion in the results of this study is that there is an effect of online learning on student learning outcomes during the pandemic at Kassi Public Elementary School, Makassar City.